Combining forest structure data and fuel modelling to classify fire hazard in Portugal (Annals of Forest Science, 2009)
• Fire management activities can greatly beneﬁt from the description of wildland fuel to assess ﬁre hazard. • A forest typology developed from the Portuguese National Forest Inventory that combines cover type (the dominant overstorey species) and forest structure deﬁned as a combination of generic stand density (closed or open) and height (low or tall) is translated into fuel models. Fire behaviour simulations that accounted for the ﬁre environment modiﬁcation induced by stand structure resulted in an objective and quantitative assessment of ﬁre hazard for 19 forest types. • The range of ﬁre risk is similar between and within cover types. Stand structure, rather than cover type, is the major determinant of ﬁre vulnerability. This indicates a potentially prominent role of stand and fuel management in wildﬁre mitigation. Four ﬁre hazard groups are deﬁned: (1) open and tall forest types, and closed and tall Quercus suber and diverse forests; (2) closed, low woodlands of deciduous oaks, Q. suber and diverse forests, closed and tall Pinus pinaster woodland and tall Eucalyptus globulus plantations; (3) open and low forest types; (4) dense low stands of P. pinaster, E. globulus and Acacia. Potential ﬁre risk increases from (1) to (4).